Reliability Based Maintenance in Hydropower: A Case Study of Bijaypur-I Small Hydropower Plant - Sharma, Rajan; Bhattarai, Nawaraj (Journal of Innovations in Engineering Education, 2020)
Reliability engineering is emerging field which provides a tools to ensure the system is capable to deliver reliable product and service to the customer. Electricity is one of the most important human needs in this modern age. So reliability of such facilities plays important role in the quality of life and the economy of the county. Hydropower is one of the main source of energy in Nepal, whose reliability plays important role to successful transaction of traditional fuel to electricity to ensure the targeted energy consumption by government of Nepal in fifteenth five year plan. So this paper foster the way of improving the reliability of hydropower plant to ensure the reliability of power supply in National grid. As the study carried out in Bijayapur-I small Hydropower plant, the reliability and availability found as 0.876 and 0.793 only and insufficient flow seems the major contribution to decrease reliability as scheduled outage, whereby problem in turbine section plays important role to reduce the reliability in the electromechanical system of the plant whose contribution in reliability and availability is 79% so any failure in turbine section adversely affects the performance of plant. Due to this the maintenance strategy should be focused on turbine section. And the study recommended to increase the frequency of flushing of radial filter of cooling system, redundancy in filter system can increase the reliability, use of cyclone separator to separate the dissolved limestone and dissolved sand is the another option, and to use close loop cooling system instead of open system.